ANALISIS PERBANDINGAN KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA MENGGUNAKAN MEDIA AUDIO VISUAL DENGAN MENGGUNAKAN TEKS PADA MATERI PECAHAN KELAS IV SDN 13 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find out the comparison of students' difficulties in solving story problems using audio-visual media using text on the fractional material for class IV SDN 13 Pekanbaru. The research subjects were all fourth grade students at SDN 13 Pekanbaru, totaling 24 students. 12 students were given questions using audio-visual media and 12 students were given questions using text by taking interview samples totaling 7 students. The data used in this study are primary data obtained directly from sources and secondary data obtained from available sources. Data analysis is the process of systematically searching and compiling data, data obtained from interviews, observations, and documentation, by organizing the data into categories, describing them into units, synthesizing, compiling into patterns, choosing what is important and what is important. that will be studied, and make conclusions so that they are easily understood by themselves. The result of this research is the difficulty of using audio-visual media more than using text. This can be proven by using comparative analysis data on students' difficulties in solving math story problems using audio-visual media using text on fractions material in class IV SDN 13 Pekanbaru.Key Words: Learning Difficulties, Audio Visual Media, Text.